Neuron-Glia Crosstalk Plays a Major Role in the Neurotoxic Effects of Ketamine via Extracellular Vesicles - Penning, Donald H.; Cazacu, Simona; Brodie, Aharon; Jevtovic-Todorovic, Vesna; Kalkanis, Steve N.; Lewis, Michael; Brodie, Chaya (Frontiers in Cell and Developmental Biology, 2021)
Background: There is a compelling evidence from animal models that early exposure to clinically relevant general anesthetics (GAs) interferes with brain development, resulting in long-lasting cognitive impairments. Human studies have been inconclusive and are challenging due to numerous confounding factors. Here, we employed primary human neural cells to analyze ketamine neurotoxic effects focusing on the role of glial cells and their activation state. We also explored the roles of astrocyte-derived extracellular vesicles (EVs) and different components of the brain-derived neurotrophic factor (BDNF) pathway. Methods: Ketamine effects on cell death were analyzed using live/dead assay, caspase 3 activity and PARP-1 cleavage. Astrocytic and microglial cell differentiation was determined using RT-PCR, ELISA and phagocytosis assay. The impact of the neuron-glial cell interactions in the neurotoxic effects of ketamine was analyzed using transwell cultures. In addition, the role of isolated and secreted EVs in this cross-talk were studied. The expression and function of different components of the BDNF pathway were analyzed using ELISA, RT-PCR and gene silencing. Results: Ketamine induced neuronal and oligodendrocytic cell apoptosis and promoted pro-inflammatory astrocyte (A1) and microglia (M1) phenotypes. Astrocytes and microglia enhanced the neurotoxic effects of ketamine on neuronal cells, whereas neurons increased oligodendrocyte cell death. Ketamine modulated different components in the BDNF pathway: decreasing BDNF secretion in neurons and astrocytes while increasing the expression of p75 in neurons and that of BDNF-AS and pro-BDNF secretion in both neurons and astrocytes. We demonstrated an important role of EVs secreted by ketamine-treated astrocytes in neuronal cell death and a role for EV-associated BDNF-AS in this effect. Conclusions: Ketamine exerted a neurotoxic effect on neural cells by impacting both neuronal and non-neuronal cells. The BDNF pathway and astrocyte-derived EVs represent important mediators of ketamine effects. These results contribute to a better understanding of ketamine neurotoxic effects in humans and to the development of potential approaches to decrease its neurodevelopmental impact.